Equal channel angular pressing of the aluminium alloy: A numerical investigation. (2020) - Mishra, Binayak; Kumar Mohapatra, Sambit; Ranjan, Vikas; Maity, Kalipada
Abstract: Equal channel angular pressing (ECAP) is adopted as the most popular bulk severe plastic deformation (SPD) processing technique and has been utilised for the grain refinement in several metals and alloys. The aforesaid technique, in which the metallic billet processes through a simple shear was investigated by finite element analysis in this work. The die channel angle for the investigation was selected by considering the minimum energy consumption for the induction of maximum uniform strain. Out of preferred channels, 110° was found suitable. Al-6063 was considered as work material. Maximum load requirement for accomplishing the operation, effective stress and strain distribution were also inquired. The mathematically calculated equivalent plastic strain value found in close proximity to the value obtained from the FEA. In the process die channel angle and friction conditions are primarily responsible for maximum strain induction in the work material, which was affirmed here by the numerical analysis. In addition to it these two parameters influence the maximum load requirement for accomplishing the operation whereas, ram rate within the investigated range has the negligible impact.